Peningkatan Kemampuan Sosial Emosional Melalui Permainan Kolaboratif pada Anak KB - Rizki Ananda; Fadhilaturrahmi Fadhilaturrahmi (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
This research begins with the finding that children in the Tuanku Tambusai Play Group tend to experience obstacles in their emotional-social development. On observations made do not look like children are willing to play with peers in one group, the child still shows ego or self-winding attitude, the child can not cooperate with members of his group, still shows the attitude of competing in the play, and the child is not responsible for doing According to the findings, the researcher intends to develop children's emotional social abilities with the application of collaborative games. The research method used is action research. Methods were performed using Kemmis and Taggart's model cycles consisting of 4 stages (planning, action, observation, and reflection). The child's emotional social developmental data in learning was obtained from observations and documentation analyzed by percentage. Research conducted two cycles, each cycle is implemented in three meetings. The results show through collaborative games can improve emotional-social development in children Tuanku Tambusai Play Group